Linking inherent O-Linked Protein Glycosylation of YghJ to Increased Antigen Potential - Thorsing, Mette; Krogh, Thøger Jensen; Vitved, Lars; Nawrocki, Arkadiusz; Jakobsen, Rikke; Larsen, Martin R.; Chakraborty, Subhra; Bourgeois, A. Louis; Andersen, Ann Zahle; Boysen, Anders (Frontiers in Cellular and Infection Microbiology, 2021)
Enterotoxigenic Escherichia coli (ETEC) is a WHO priority pathogen and vaccine target which causes infections in low-income and middle-income countries, travelers visiting endemic regions. The global urgent demand for an effective preventive intervention has become more pressing as ETEC strains have become increasingly multiple antibiotic resistant. However, the vaccine development pipeline has been slow to address this urgent need. To date, vaccine development has focused mainly on canonical antigens such as colonization factors and expressed toxins but due to genomic plasticity of this enteric pathogen, it has proven difficult to develop effective vaccines. In this study, we investigated the highly conserved non-canonical vaccine candidate YghJ/SsLE. Using the mass spectrometry-based method BEMAP, we demonstrate that YghJ is hyperglycosylated in ETEC and identify 54 O-linked Set/Thr residues within the 1519 amino acid primary sequence. The glycosylation sites are evenly distributed throughout the sequence and do not appear to affect the folding of the overall protein structure. Although the glycosylation sites only constitute a minor subpopulation of the available epitopes, we observed a notable difference in the immunogenicity of the glycosylated YghJ and the non-glycosylated protein variant. We can demonstrate by ELISA that serum from patients enrolled in an ETEC H10407 controlled infection study are significantly more reactive with glycosylated YghJ compared to the non-glycosylated variant. This study provides an important link between O-linked glycosylation and the relative immunogenicity of bacterial proteins and further highlights the importance of this observation in considering ETEC proteins for inclusion in future broad coverage subunit vaccine candidates.